The Defensive Golden Index: A novel method to rank football player defensive performance for Fútbol Club Barcelona - Ferreira, R.; Pereira, S.; Ribeiro, J.; Garganta, J.; Barreira, D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
This study sought to create a formula called the Defensive Golden Index (DGI) that assigns an index to each player according to his individual and collective defensive performance. This method helps identify the best-ranked players in defending play, designated as Defensive Golden Players. The study was organized in two main phases: (1) selection, definition, and validation, including weighting assignment, of a set of variables associated with players` defensive performance by applying statistical techniques to standardize variable values that compose the DGI formula; and (2) applicability of the DGI formula to rank players` performance of Fútbol Club Barcelona (FCB) according to the opponents` level in 38 games of La Liga 2018-2019. A set of variables (e.g. tackles, anticipation, successful interception, successful 1 × 1 defensive) were included in a questionnaire and (re)conceptualized based on previous literature and author`s experience as coaches and match analysts. The survey was reviewed by 11 football experts to ascertain the importance of variables, as well as validate and determine the weight of each variable. Each defensive variable was divided by the time played. Then the individual values were subtracted from the mean and divided by the standard deviation of the variable. The results of the DGI formula were obtained by multiplying the weights from the experts for each of the 12 standardized defensive variables by the sum of each variable. In general, the best-ranked FCB players (Defensive Golden Players) were Gerard Piqué, Clement Lenglet, and Sergio Busquets. Moreover, considering the opponents` levels, the same players were best-ranked, however, with different order in the top three positions. The DGI formula is a valuable method for capturing individual and collective performance of football players in defending play.